¿Another wayto tell stories? (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
It is often said that in the Odyssey all human thought is and fits. It is the journey of journeys, life, and therefore nothing escapes the Homeric poem, whether they are questions of philosophy, politics, ethics or culture. For a student of narrative, in particular, the story of Odysseus is the mold from which all possible stories come. And most importantly, the forge from which all the possible ways of telling those stories come out. Even the ones that don't exist yet. Homer is adventure and mystery, tragedy and drama, emotion and delay. He is "narrating for the pleasure of narrating" (García Gual, 2015, p. XI), and from that irrepressible passion that feeds his verses, the infinite branches of the tree of narratology flourish. The 14 selected articles, out of a total of almost 40 contributions received, that can be read in this issue of ASRI navigate those rivers that flow into that great "flow of images" that makes up contemporaneity, and which the previous one dealt with so well number of our magazine.
Keywords: New Narratives